The relationships between emerging adults self-efficacy and motivation levels and physical activity: a cross-sectional study based on the self-determination theory - Tao, Yuexian; Xu, Tao; Wang, Xin; Liu, Chengyi; Wu, Yinyin; Liu, Mingyue; Xiao, Ting; Qiu, Xinze (Frontiers in Psychology, 2024)
Objectives The study aims to examine the associations between exercise self-efficacy, motivation, physical activity, and body composition among emerging adults. Design Cross-sectional. Methods A convenience sample of 147 emerging adults participated in the Releasing Weight (RELEW) project. The InBody720 analyzer was used to measure body composition, and the International Physical Activity Questionnaire-Short, the Shortened Physical Activity Self-Efficacy Scale, and the Treatment Self-Regulation Questionnaire were used to measure self-reported physical activity, self-efficacy, and motivation. Structural Equation Modeling was used to exam the complex relationships among multiple variables. in this study. The Partial least squares structural equation modeling analysis with bootstrapping in Smart PLS 3 was employed to explore the path coefficients and t-values for the relationships that were thought to exist. Significance was determined using a threshold of p < 0.05. Results The mean age of 147 participants was 18.5 ± 1.87, of whom 51.7% were female, recruited for this study. Exercise self-efficacy has a significant positive correlation with exercise motivation (r = 0.220, p = 0.008) and physical activity (r = 0.279, p < 0.001). Exercise motivation does not demonstrate significant associations with physical activity (r = 0.094, p = 0.298). Utilizing SEM, the model explained 9.2% of exercise self-efficacy, 11.8% of physical activity, and 68.3% of body composition variance. Mediation analysis revealed that exercise self-efficacy partially mediated the relationship between exercise motivation and physical activity (β = 0.106, t = 2.538, p < 0.05), and physical activity partially mediated the relationship between exercise self-efficacy and body composition (β = −0.296, t = 4.280, p < 0.001). Conclusion This study sheds light on the complex relationships among motivation, self-efficacy, physical activity and body composition during emerging adulthood. Our results highlight the mediating role of self-efficacy and its impact on physical activity behaviors, offering valuable insights for targeted interventions and policy development to improve health outcomes in this demographic.